PANDAI BESI DI KELURAHAN TOLOA KECAMATAN TIDORE SELATAN KOTA TIDORE KEPULAUAN - Dukomalamo, Syharil (Universitas Sam Ratulangi, 2012)
Blacksmiths are in Tidore Kepualaun is one creative or economic livelihood in the village Toloa. Blacksmiths relatively small industry that has contributed to the community in the village such as the land jobs for the workforce. They still stick with using the equipment that is still relatively modest. They are also confronted with production manufacturers that are sold in stores are more varied shape and style. But it is, is not an obstacle for them to keep producing. To capitalize the knowledge that has been passed down by ancestors and social capital which is always held in high esteem by every employee so that they still survive even with its limitations both in terms of equipment and financial. Keywords: blacksmith, technology, culture